Leveling the field for biofuels: Comparing the economic and environmental impacts of biofuel and other export crops in Malawi - Schuenemann, Franziska; Thurlow, James; Zeller, Manfred (International Food Policy Research Institute, 2016)
Biofuel production can have conflicting impacts on economic growth, food and energy security, and natural resources. Understanding these trade-offs is crucial for designing policies that are consistent with the Sustainable Development Goals. This is particularly true in low-income countries, where the need to promote both energy and food security is most pressing. To this end, we develop an integrated modeling framework to simultaneously assess the economic and environmental impacts of producing biofuels in Malawi. We extend earlier studies by incorporating the effects of land use change on crop water use, and the opportunity costs of using scarce agricultural resources for biofuels rather than other export crops. We find that biofuel production is generally pro-poor and reduces food insecurity by raising household incomes. Irrigated outgrower schemes rather than estate farms lead to better economic outcomes, fewer greenhouse gas emissions, and similar crop water requirements. Nevertheless, Malawi must reduce emissions from its ethanol plants in order to access European markets. We also find that the economic and environmental impacts of biofuels are preferable to those of tobacco or soybeans. The European Union has raised the standards expected of biofuel producers, but it should “level the playing field” by applying similar standards to other export crops from developing countries.